A flame-retardant phase change electrolyte based on acetylenic monomer and its irradiation preparation method
Patent Information
- Application Number
- CN202610826546.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-09-22
AI Technical Summary
[0002]然而,现有阻燃型GPE在应用中仍面临瓶颈:阻燃剂的引入常降低离子传导效率,导致电池动力学性能受损;常规聚合物网络难以抑制高镍正极与锂金属界面副反应,长循环稳定性差
1)相变电解质兼具固态电解质的结构稳定性和液态电解质的高离子导电性,既能有效隔离电子传输、保障电池正常充放电,又能促进锂离子快速迁移;通过原位聚合方式在电池内部形成,相变电解质与正、负极界面接触紧密,界面阻抗低,可减少界面副反应的发生,提升电池的循环稳定性。
Smart Images

Figure CN122800725A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to a flame-retardant phase change electrolyte based on an alkyne-containing monomer and its irradiation preparation method. Technical Background Lithium metal batteries have extremely high theoretical energy density (3860 mAh·g). -1 Gel polymer electrolytes (GPEs) are widely recognized as the next-generation core technology direction for breaking through the bottleneck of large-capacity energy storage. By in-situ polymerization to lock in liquid electrolytes, GPEs combine the high ion transport rate of liquid electrolytes with the structural stability of solid electrolytes. They are expected to solve the problems of flammability, easy lithium deposition, and poor safety of liquid electrolytes, while also solving the problems of low ionic conductivity and high solid-solid interface impedance of solid electrolytes. They are the most ideal compromise solution at present.
[0002] However, existing flame-retardant GPEs still face bottlenecks in application: the introduction of flame retardants often reduces ion conduction efficiency, leading to impaired battery kinetic performance; conventional polymer networks struggle to suppress side reactions at the interface between the high-nickel cathode and lithium metal, resulting in poor long-cycle stability. Therefore, developing in-situ polymerized phase change electrolytes that combine high flame retardancy, high ion conductivity, and excellent interfacial stability is of great significance for achieving a synergistic improvement in the safety and electrochemical performance of lithium metal batteries. Summary of the Invention
[0003] This invention aims to prepare a novel flame-retardant phase change electrolyte based on triargyl phosphate (TPP) and pentaerythritol tetraacrylate (PETEA) using a gamma-ray irradiation method. By introducing functional monomers containing alkyne groups (-C≡C-), and utilizing their high bond energy and linear molecular configuration, a three-dimensional cross-linked network with high mechanical modulus, excellent thermal stability, and high flame-retardant properties is constructed in situ inside the battery. This achieves a stable electrolyte system that can effectively restrict electron transport and synergistically promote efficient lithium-ion conduction.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a flame-retardant phase change electrolyte (P) based on an alkyne-containing monomer. x -PETEA y ) z -The preparation method of GPE, where P represents triargyl phosphate (TPP) and PETEA represents pentaerythritol tetraacrylate. x This represents the mass fraction of triargyl phosphate relative to the total mass of the polymer monomers. y This represents the mass fraction of pentaerythritol tetraacrylate relative to the total mass of the polymer monomers. z The gel fraction after polymerization includes the following steps: S1: Weigh triargyl phosphate (TPP) and pentaerythritol tetraacrylate (PETEA) at a mass ratio of 1:9 to 7:3, add them together to the lithium salt electrolyte, and mix thoroughly until the monomers are completely dissolved to obtain a homogeneous and transparent precursor solution; the corresponding ratio is... x The value range is 10% to 70%. y The value range is 30% to 90%. z The value of z is in the range of 0 to 1; the preferred value of z is 0.4 to 1. The concentration of the lithium salt electrolyte is 0.5~3 mol / L; S2: Irradiate the precursor solution described in step S1 with γ-rays to cause TPP and PETEA to undergo a copolymerization reaction, initiating a transition from the liquid phase to the gel phase, and obtaining the flame-retardant phase change electrolyte; the irradiation absorbed dose rate is 25~30 Gy / min, and the absorbed dose is 1~5 kGy.
[0005] Preferably, the sum of the masses of tripropargyl phosphate (TPP) and pentaerythritol tetraacrylate (PETEA) accounts for 1 to 10% of the total mass of the precursor solution.
[0006] Preferably, the lithium salt electrolyte is a lithium hexafluorophosphate electrolyte with a concentration of 1.0 mol / L; the solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 10% by mass of fluoroethylene carbonate (FEC) is added.
[0007] Preferably, in step S2, the radiation source that generates the γ-rays is... 60 Co source.
[0008] Preferably, in step S1, the mixture is stirred until homogeneous; the stirring speed is 500~600 rpm, and the stirring time at room temperature is 4-6 h.
[0009] Preferably, in step S2, the precursor solution is placed in a transparent container for irradiation; the container material is selected from radiation-resistant materials such as glass bottles and polytetrafluoroethylene bottles.
[0010] Preferably, in step S2, the irradiation time is 35~200 min.
[0011] Secondly, the present invention provides a (P) synthesized by the method described in the first aspect. x -PETEA y ) z -GPE.
[0012] Thirdly, the present invention provides a (P) synthesized by the method described in the second aspect. x -PETEA y )z -GPE is used in lithium metal battery electrolytes.
[0013] Preferably, the lithium metal battery uses a lithium sheet as the negative electrode and NCM85 material as the positive electrode.
[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) Phase change electrolytes combine the structural stability of solid electrolytes with the high ionic conductivity of liquid electrolytes. They can effectively isolate electron transport and ensure normal charging and discharging of the battery, while also promoting the rapid migration of lithium ions. Formed inside the battery through in-situ polymerization, the phase change electrolyte has close contact with the positive and negative electrode interfaces, resulting in low interfacial impedance, which can reduce the occurrence of interfacial side reactions and improve the cycle stability of the battery.
[0015] 2) Tripropyne phosphate (TPP), as a phosphorus-containing monomer, possesses unsaturated carbon-carbon triple bonds (-C≡C-), which can participate in radiation-induced free radical polymerization reactions. The phosphorus-containing groups can not only inhibit combustion at high temperatures through gas-phase flame retardancy and solid-phase char formation mechanisms, but their strong polarity also facilitates the dissociation of lithium salts, increases the lithium-ion transference number, and thus improves the electrochemical performance of the battery. Pentaerythritol tetraacrylate (PETEA), as a multifunctional monomer, forms a stable cross-linked gel skeleton structure after polymerization, which can bind electrolyte molecules and reduce the risk of volatilization and leakage. The phase change electrolyte formed by the combination of the two reduces the probability of thermal runaway of lithium-ion batteries from the root, significantly improving the safety performance of the battery.
[0016] 3) The polymerization reaction is initiated by gamma ray irradiation, with the activation energy close to zero. It can be carried out gently at room temperature without the need to add any chemical initiators, crosslinking agents or catalysts, thus avoiding the adverse effects of chemical reagent residues on electrolyte purity and battery performance. At the same time, the polymerization rate and crosslinking degree can be precisely controlled by adjusting parameters such as irradiation dose rate and absorbed dose. The process is highly controllable, simple to operate, and suitable for large-scale production. Attached Figure Description
[0017] Figure 1 This is the nuclear magnetic resonance P-spectrum (NMR-P) of the carbon-carbon triple bond-containing polymer monomer tripropyne phosphate (TPP).
[0018] A represents chemical shift in ppm, and B represents intensity.
[0019] Figure 2 This disclosure is based on a novel flame retardant (P) with carbon-carbon triple bonds. x -PETEA y ) z -GPE nuclear magnetic resonance P spectrum (NMR-P).
[0020] A represents chemical shift in ppm, and B represents intensity.
[0021] Figure 3 This disclosure is based on a novel flame retardant (P) with carbon-carbon triple bonds. x -PETEA y ) z - Fourier transform infrared (FTIR) spectrum of GPE.
[0022] A represents the wave number, measured in cm. -1 B represents light transmittance, expressed in units of %.
[0023] Figure 4 This disclosure is based on a novel flame retardant (P) with carbon-carbon triple bonds. x -PETEA y ) z - Comparison of long-term cycling of lithium metal half-cells assembled with GPE and liquid electrolyte under conditions of 3~4.3 V, 0.5 C.
[0024] A represents the number of cycles, B represents the specific capacity in mAh / g, and C represents the coulombic efficiency in _____. Detailed Implementation
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0027] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0028] Example 1 A novel flame retardant based on carbon-carbon triple bonds (P x -PETEA y ) z The preparation method and application of phase change electrolytes are as follows: In a glass vial containing 9.7 g of commercial electrolyte (1.0 M LiPF6 in EC:DEC = 1:1 Vol% with 10% FEC), 0.12 g of triargyl phosphate monomer and 0.18 g of pentaerythritol tetraacrylate monomer were added. The mixture was stirred for 4 h at 600 rpm to obtain a precursor solution. This solution was then subjected to gamma irradiation in a cobalt source chamber at a dose rate of 29.5 Gy / min, an absorbed dose of 3 kGy, and an irradiation time of 105 min. The resulting product was named (P...). 40 -PETEA 60 ) 0.915 -GPE, where x =40, y =60%, z =0.915 ( x This represents the mass fraction of propyltriethynyl phosphate in the total polymer monomers, which is 0.3 g. y This represents the mass fraction of pentaerythritol tetraacrylate in the total polymer monomers, which is 0.3 g. z (Represents gel fraction).
[0029] The polymer monomer tripropyne phosphate (TPP) used in this invention was characterized by phosphorus NMR spectroscopy, such as... Figure 1 As shown, Figure 1 The a in the formula corresponds to the P element, which indicates that the chemical environment of the P element in this monomer is unique.
[0030] Regarding the present invention (P) x -PETEA y ) z -GPE was used for phosphorus NMR characterization, such as Figure 2 As shown, Figure 2 In the middle, ae corresponds to the synthesized (P) x -PETEA y ) z - The phosphorus element corresponding to GPE material. Comparison of the NMR phosphorus spectrum with that of TPP material. Figure 2 In 31 The multiple peaks of P NMR, which are not unique, indicate that the chemical environment around P is not unique and that there are C skeletons with different degrees of crosslinking, proving that TPP participates in network polymerization.
[0031] Figure 3 Yes (P) x -PETEA y ) z - Fourier transform infrared (FTIR) spectra of GPE and monomers, I is TPP, II is PETEA, III is (P x -PETEA y ) z-GPE. The polymer monomer PETEA is at 1639 cm⁻¹. -1 A strong characteristic peak of carbon-carbon double bond (-C=C-) appears at 2130 cm⁻¹; the monomer TPP shows a peak at 2130 cm⁻¹. -1 A characteristic peak for a carbon-carbon triple bond (-C≡C-) appears nearby. Comparing this to the infrared peaks of phase-change electrolytes, a peak at 2130 cm⁻¹ is observed. -1 The -C≡C- peak corresponding to TPP completely disappears at 1639 cm⁻¹. -1 The -C=C- peak corresponding to PETEA is retained and shifts to higher wavenumbers. This is because the -C≡C- of TPP participates in the polymerization reaction to generate some -C=C-, and the chemical environment of the double bond changes due to the altered gel network structure formed by polymerization, being affected by the electronic effects of the surrounding cross-linked backbone. The above peak shape changes indicate that under γ-ray irradiation conditions, the -C≡C- of TPP fully participates in the polymerization reaction, and partially generates -C=C-, while the -C=C- of PETEA partially participates in cross-linking to form a gel network. Both have successfully undergone polymerization, proving that (P... x -PETEA y ) z -GPE material was successfully prepared.
[0032] TPP and PETEA were added to a commercial electrolyte (1.0 M LiPF6 in EC: DEC = 1:1 Vol% with 10% FEC) and stirred until homogeneous to obtain a precursor electrolyte. The precursor electrolyte was injected into a lithium metal battery with NCM85 as the positive electrode, lithium sheet as the negative electrode, and Celgard2500 separator. The encapsulated battery was then subjected to γ-irradiation at a dose rate of 29.5 Gy / min, an absorbed dose of 3 kGy, and an irradiation time of 105 min. Finally, the electrochemical performance of the irradiated in-situ polymerized gel battery was tested using the Newway charge / discharge system.
[0033] like Figure 4 As shown, lithium metal batteries irradiated at a dose of 3 kGy and then left to stand for 10 h were tested under conditions of 3–4.3 V, 0.5 C rate, and 25 °C. It can be clearly seen that after 300 cycles at 0.5 C rate, the flame-retardant phase change electrolyte (P...)... 40 -PETEA 60 ) 0.915 -GPE exhibits a capacity retention of 84%, while commercial electrolytes retain 73.62%. Compared to commercial liquid electrolytes, it demonstrates higher capacity retention and better charge-discharge cycle stability. Furthermore, its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0034] Example 2 In Example 1 x Change to 10%, yThe percentage was changed to 90%, and other conditions remained the same as in Example 1, resulting in sample (P). 10 -PETEA 90 ) 0.965 -GPE. Its SET is 298.5 s / g, and its flame retardancy efficiency is 42.09%.
[0035] Example 3 In Example 1 x Change to 20%, y The percentage was changed to 80%, and other conditions remained the same as in Example 1, to obtain sample (P). 20 -PETEA 80 ) 0.952 -GPE. Its SET is 241.2 s / g, and its flame retardant efficiency is 68.02%.
[0036] Example 4 In Example 1 x Change to 30%, y The percentage was changed to 70%, and other conditions remained the same as in Example 1, to obtain sample (P). 30 -PETEA 70 ) 0.938 -GPE. Its SET is 132.8 s / g, and its flame retardant efficiency is 91.63%.
[0037] Example 5 In Example 1 x Change to 50%, y The percentage was changed to 50%, and other conditions remained the same as in Example 1, resulting in sample (P). 50 -PETEA 50 ) 0.885 -GPE. Its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0038] Example 6 In Example 1 x Change to 60%, y The concentration was changed to 40%, the absorbed dose was changed to 4 kGy, and other conditions were the same as in Example 1, resulting in sample (P). 60 -PETEA 40 ) 0.892 -GPE. Its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0039] Example 7 In Example 1 x Change to 60%, y The concentration was changed to 40%, the absorbed dose was changed to 5 kGy, and other conditions were the same as in Example 1, to obtain sample (P). 60 -PETEA 40 ) 0.92-GPE. Its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0040] Example 8 In Example 1 x Change to 70%, y The concentration was changed to 30%, the absorbed dose was changed to 5 kGy, and other conditions were the same as in Example 1, to obtain sample (P). 70 -PETEA 30 ) 0.855 -GPE. Flame retardant efficiency is 100%.
[0041] Example 9 The absorbed dose in Example 1 was changed to 1 kGy, and other conditions remained the same as in Example 1, to obtain sample (P). 40 -PETEA 60 ) 0.42 -GPE. Its SET is 15.0 s / g, and its flame retardancy efficiency is 95%.
[0042] Example 10 The absorbed dose in Example 1 was changed to 1.5 kGy, and other conditions remained the same as in Example 1, to obtain sample (P). 40 -PETEA 60 ) 0.58 -GPE. Its SET is 8.0 s / g, and its flame retardant efficiency is 98.0%.
[0043] Example 11 The absorbed dose in Example 1 was changed to 2 kGy, and other conditions remained the same as in Example 1, to obtain sample (P). 40 -PETEA 60 ) 0.75 -GPE. Its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0044] Example 12 The absorbed dose in Example 1 was changed to 2.5 kGy, and other conditions remained the same as in Example 1, to obtain sample (P). 40 -PETEA 60 ) 0.86 -GPE. Its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0045] Example 13 The absorbed dose in Example 1 was changed to 3.5 kGy, and other conditions remained the same as in Example 1, to obtain sample (P). 40 -PETEA 60 ) 0.935 -GPE. Its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0046] Example 14 The absorbed dose in Example 1 was changed to 4 kGy, and other conditions remained the same as in Example 1, to obtain sample (P). 40 -PETEA 60 ) 0.955 -GPE. Its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0047] Example 15 The absorbed dose in Example 1 was changed to 4.5 kGy, and other conditions remained the same as in Example 1, to obtain sample (P). 40 -PETEA 60 ) 0.97 -GPE. Its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0048] Example 16 The absorbed dose in Example 1 was changed to 5 kGy, and other conditions remained the same as in Example 1, to obtain sample (P). 40 -PETEA 60 ) 0.982 -GPE. Its SET is 0 s / g, and its flame retardant efficiency is 100%.
[0049] Comparison sample A commercial liquid electrolyte was used as a control sample, without the addition of TPP and PETEA. Its SET was 468.8 s / g, and its flame retardant efficiency was 0%.
[0050] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Those skilled in the art can make various modifications to the technical solutions in the embodiments based on the above description. It is neither necessary nor possible to exhaustively describe all possible implementations. Any modifications, variations, substitutions, etc., made based on the technical content disclosed in this invention are equivalent to equivalent implementations and should be included within the protection scope of this invention.
Claims
1. A flame-retardant phase change electrolyte (P) based on an alkyne-containing monomer. x -PETEA y ) z The preparation method of -GPE is characterized by, P represents propargyl phosphate, and PETEA represents pentaerythritol tetraacrylate. x This represents the mass fraction of triargyl phosphate relative to the total mass of the polymer monomers. y This represents the mass fraction of pentaerythritol tetraacrylate relative to the total mass of the polymer monomers. z The gel fraction after polymerization includes the following steps: S1: Weigh triargyl phosphate (TPP) and pentaerythritol tetraacrylate (PETEA) at a mass ratio of 1:9 to 7:3, add them together to the lithium salt electrolyte, and mix thoroughly until the monomers are completely dissolved to obtain a homogeneous and transparent precursor solution; the corresponding ratio is... x The value range is 10% to 70%. y The value range is 30% to 90%. z The value range is 0 to 1; S2: Irradiate the precursor solution described in step S1 with γ-rays to cause TPP and PETEA to undergo a copolymerization reaction, thereby obtaining the flame-retardant phase change electrolyte; the irradiation absorbed dose rate is 25~30 Gy / min, and the absorbed dose is 1~5 kGy.
2. The flame-retardant phase change electrolyte (P) based on an alkyne-containing monomer as described in claim 1 x -PETEA y ) z The preparation method of -GPE is characterized by, The sum of the masses of triargyl phosphate (TPP) and pentaerythritol tetraacrylate (PETEA) accounts for 1-10% of the total mass of the precursor solution; the concentration of the lithium salt electrolyte is 0.5-3 mol / L.
3. The flame-retardant phase change electrolyte (P) based on an alkyne-containing monomer as described in claim 1 x -PETEA y ) z The preparation method of -GPE is characterized by, The lithium salt electrolyte is lithium hexafluorophosphate electrolyte with a concentration of 1.0 mol / L; the solvent is a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, with 10% fluoroethylene carbonate added by mass.
4. The flame-retardant phase change electrolyte (P) based on an alkyne-containing monomer as described in claim 1 x -PETEA y ) z The preparation method of -GPE is characterized by, In step S2, the radiation source that produces the γ rays is 60 Co source.
5. The flame-retardant phase change electrolyte (P) based on an alkyne-containing monomer as described in claim 1 x -PETEA y ) z The preparation method of -GPE is characterized by, In step S1, the mixture is stirred until homogeneous; the stirring speed is 500~600 rpm, and the stirring time at room temperature is 4-6 h.
6. The flame-retardant phase change electrolyte (P) based on an alkyne-containing monomer as described in claim 1 x -PETEA y ) z The preparation method of -GPE is characterized by, In step S2, the precursor solution is placed in a transparent container for irradiation; the container material is selected from glass and polytetrafluoroethylene.
7. The flame-retardant phase change electrolyte (P) based on an alkyne-containing monomer as described in claim 1 x -PETEA y ) z The preparation method of -GPE is characterized by, In step S2, the irradiation time is 35~200 min.
8. A (P) synthesized by the method according to any one of claims 1 to 7 x -PETEA y ) z -GPE.
9. A (P) synthesized by the method of claim 8 x -PETEA y ) z -GPE is used in lithium metal battery electrolytes.
10. The application according to claim 9, characterized in that, The lithium metal battery uses lithium foil as the negative electrode and NCM85 material as the positive electrode.